Pengaruh E-commerce, Pengetahuan Akuntansi dan Sistem Informasi Akuntansi Terhadap Kinerja UMKM - Sintia Maya; Anggun Permata Husda (Komunitas Dosen Indonesia, 2024)
MSMEs are of paramount importance in the economic landscape of a nation. The performance of Micro, Small, and Medium Enterprises (MSMEs) pertains to the extent to which these firms successfully accomplish their economic and business goals. The objective of this study is to determine and examine the impact of e-commerce, accounting expertise, and accounting information systems on the performance of MSMEs. The study used a quantitative research methodology, with a sample size of 135 participants selected using the Slovin formula. The technique of purposive sampling is employed for participant selection. Data collection entails the dissemination of questionnaires employing Likert scales, followed by analysis using SPSS Version 26. Based on the results, it can be concluded that the performance of MSMEs is significantly influenced by the e-commerce factor, as supported by a T-test significance value of 0.004, which falls below the predetermined threshold of 0.05. However, the significance value of 0.548 from the T-test indicates that the variable of accounting expertise does not significantly affect the performance of MSMEs. This value exceeds the predetermined threshold of 0.05. In addition, the significance value of 0.000 for the T-test on accounting information systems means that this variable has a substantial effect on the performance of MSMEs; this value is less than the critical value of 0.05. Hence, it can be deduced that the performance of micro, small, and medium enterprises (MSMEs) is significantly impacted by the variables of e-commerce and accounting information systems. Nonetheless, there is no discernible effect of accounting expertise on the performance of MSMEs.